A high-resolution, 1250-year long drought record from Ea Tyn Lake, Central Highlands of Việt Nam - Nguyễn-Đình, Thái; Nguyễn-Thùy, Dương; Nguyễn-Văn, Hướng; Ojala, Antti EK; Đỗ-Trọng, Quốc; Phan-Thanh, Tùng; Nguyễn Thị, Hồng; Thị Ánh Nguyễn, Nguyệt; Xuân Đinh, Thành; Thị Huyền Nguyễn, Trang; Sauer, Peter E.; Schimmelmann, Arndt; et al. (The Holocene, 2022)
An understanding of past climatic variability at regional to local scales is mandatory for a proper evaluation of current and potential future repercussions from global climate change. The Southeast Asian tropics remain severely under-represented in paleoenvironmental and paleoclimatic reconstructions, although a few recent paleoclimate studies evaluated the variability, position and strength of the main Asian monsoon systems at different timescales from modern records to the last 15,000 years. Comparable data from Việt Nam, however, are scarce although Việt Nam and its Central Highlands are critically located at the intersection of the East Asian Summer Monsoon and the Indian Summer Monsoon with highly important socio-ecological consequences from changes in the climate system. This study presents a high-resolution sedimentary climate record from Ea Tyn Lake in Việt Nam’s Central Highlands covering the last 1250 years. Using geochemical and sedimentological proxies and principal component analysis, we reconstructed at least 12 drought events, some of which appear to be of supraregional significance as they coincide with historically documented droughts in India, China, and Cambodia. Beyond tracking short-term climate events, the Rb/Sr elemental ratio along the Ea Tyn Lake sediment sequence reflects long-term monsoon variability throughout the last millenium, which was previously only reconstructed via δ18O speleothem records from China and India. Our Ea Tyn Lake record shows that the East Asian Summer Monsoon was relatively strong between ~1000 and 1350 cal CE and weaker between 1350 and 1850 cal CE, followed by renewed intensification after ~1850 cal CE.